A New Feature Extraction Algorithm Based on Entropy Cloud Characteristics of Communication Signals. (4th June 2015) - Li, Jingchao; Guo, Jian
Abstract : Identifying communication signals under low SNR environment has become more difficult due to the increasingly complex communication environment. Most relevant literatures revolve around signal recognition under stable SNR, but not applicable under time-varying SNR environment. To solve this problem, we propose a new feature extraction method based on entropy cloud characteristics of communication modulation signals. The proposed algorithm extracts the Shannon entropy and index entropy characteristics of the signals first and then effectively combines the entropy theory and cloud model theory together. Compared with traditional feature extraction methods, instability distribution characteristics of the signals' entropy characteristics can be further extracted from cloud model's digital characteristics under low SNR environment by the proposed algorithm, which improves the signals' recognition effects significantly. The results from the numerical simulations show that entropy cloud feature extraction algorithm can achieve better signal recognition effects, and even when the SNR is −11 dB, the signal recognition rate can still reach 100%.